Implementation of active support over time in Australia. Issue 2 (3rd April 2019) - Bigby, Christine; Bould, Emma; Beadle-Brown, Julie
ABSTRACT: Background: Research indicates the value of active support in achieving good outcomes across a number of quality of life domains for people with intellectual disabilities. However, implementation is not easy, and little research has explored why. We aimed to identify some of the factors that impact on implementation of active support in supported accommodation services. Methods: Data on the quality of active support, staff training and practice leadership were collected through staff questionnaires, observations and manager interviews, for between two and four years across six organisations. Results: Active support improved over time for more able people with intellectual disability, but not for people with higher support needs. There was a weak positive correlation between active support and (1) practice leadership scores, and (2) the percentage of staff reporting active support training. Conclusions: It is important to recognise the influence of practice leadership and staff training on the quality of support and ensure provision for these in funding schemes.